An amplification-free ultra-sensitive electrochemical CRISPR/Cas biosensor for drug-resistant bacteria detection. Issue 38 (3rd September 2021) - Suea-Ngam, Akkapol; Howes, Philip D.; deMello, Andrew J.
Abstract : An amplification-free electrochemical CRISPR/Cas biosensor utilizing silver metallization (termed E-Si-CRISPR) allows detection of methicillin-resistant Staphylococcus aureus (MRSA) with excellent sensitivity and specificity. Abstract : Continued development of high-performance and cost-effective in vitro diagnostic tools is vital for improving infectious disease treatment and transmission control. For nucleic acid diagnostics, moving beyond enzyme-mediated amplification assays will be critical in reducing the time and complexity of diagnostic technologies. Further, an emerging area of threat, in which in vitro diagnostics will play an increasingly important role, is antimicrobial resistance (AMR) in bacterial infections. Herein, we present an amplification-free electrochemical CRISPR/Cas biosensor utilizing silver metallization (termed E-Si-CRISPR) to detect methicillin-resistant Staphylococcus aureus (MRSA). Using a custom-designed guide RNA (gRNA) targeting the mecA gene of MRSA, the Cas12a enzyme allows highly sensitive and specific detection when employed with silver metallization and square wave voltammetry (SWV). Our biosensor exhibits excellent analytical performance, with detection and quantitation limits of 3.5 and 10 fM, respectively, and linearity over five orders of magnitude (from 10 fM to 0.1 nM). Importantly, we observe no degradation in performance when moving from buffer to human serum samples, and achieve excellent selectivity for MRSA in human serum in the presence of other common bacteria. The E-Si-CRISPR method shows significant promise as an ultrasensitive field-deployable device for nucleic acid-based diagnostics, without requiring nucleic acid amplification. Finally, adjustment to a different disease target can be achieved by simple modification of the gRNA protospacer.